2018
DOI: 10.17707/agricultforest.64.4.06
|View full text |Cite
|
Sign up to set email alerts
|

THE ESSENTIAL OIL EXTRACTED FROM Thymus kotschyanus BOISS. & HOHEN AS A NATURAL SUBSTANCE FOR MANAGEMENT OF THE LESSER GRAIN BORER, Rhyzopertha dominica F.

Abstract: Plant essential oils as promising bio-rational agents have been considered for management of damaging insect pests because they are naturally biodegradable and safe to the non-target organisms. In the present study, the fumigant toxicity of essential oil from Thymus kotschyanus aerial parts was assessed against a major Coleopteran insect pest Rhyzopertha dominica and this bio-effect was optimised and modelled using Response Surface Methodology (RSM).Optimization of the fumigant toxicity displayed a concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The negative signs were also showed the diminishing effect of the variables on the insect mortality. Further, optimization of the fumigant toxicity revealed that a concentration of 24.62 μl/l and 57.98 h-exposure time was sufficient to kill 50% of tested insect population (Ebadollahi, 2018). In other study, modeling and optimization of the insecticidal activities of the essential oil extracted from Teucrium polium L. against T. castaneum was assessed by RSM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative signs were also showed the diminishing effect of the variables on the insect mortality. Further, optimization of the fumigant toxicity revealed that a concentration of 24.62 μl/l and 57.98 h-exposure time was sufficient to kill 50% of tested insect population (Ebadollahi, 2018). In other study, modeling and optimization of the insecticidal activities of the essential oil extracted from Teucrium polium L. against T. castaneum was assessed by RSM.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the fumigant toxicity of the essential oil of Thymus kotschyanus Boiss. & Hohen against R. dominica (Ebadollahi, 2018), and based on the high coefficient of variation value (8.02%), it was find that the presented model "52.08 + 3.49B + 22.84A -1.72AB -2.06A 2 + 3.73AB 2 -5.60A 3 " was the best for estimating the effects of independent variables (concentration (A) and time (B)) on the insect pest mortality. The negative signs were also showed the diminishing effect of the variables on the insect mortality.…”
Section: Resultsmentioning
confidence: 99%
“…In another work on the essential oil of Thymus kotschyanus Boiss. & Hohen, the optimized condition for 50% mortality against R. dominica adults was 24.62 µL/L and a 57.98-h exposure time [54]. Based on the above-mentioned results, the essential oil of T. kotschyanus was more toxic than the T. vulgaris oil.…”
Section: Methyl Eugenolmentioning
confidence: 91%
“…vulgaris, genetically, morphologically and phytochemically has a very high diversity (Nielsen et al, 2017). Phytochemical constituents of thyme mainly consist of monoterpene, sesquiterpene and phenolic compounds (Hosseini et al, 2015;Ebadollahi., 2018). Previous research shows that essential oil compositions in thyme mainly consist of thymol, carvacrol, p-cymene and c-terpinene, and their quantity changes when affected by environmental stresses (Khalil et al, 2018;Mohammadi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%